Analysis of the Implementation of Joint Funding as an Alternative Financing in the Creative Economy Sector in Indonesia - Natasya Bonita Oktaviana Manalu; Lastuti Abubakar; Tri Handayani; Dewi Kania Sugiharti (Dinasti Research, 2025)
This study analyzes the implementation of crowdfunding as an alternative financing option in Indonesia’s creative economy sector, highlighting its significant positive impact on sector growth. Crowdfunding provides broader access to capital for small and medium enterprises, enhances community engagement, and fosters innovation and product diversification. Through crowdfunding platforms, entrepreneurs can build a strong support community and introduce their creative ideas to a wider audience. Despite these benefits, the mechanism faces challenges, including a lack of understanding about crowdfunding, high competition, and regulatory uncertainty. Additionally, issues of transparency, uncertainty in achieving funding targets, as well as technological and psychological challenges must also be addressed. To maximize the benefits of crowdfunding, entrepreneurs are advised to prioritize transparency and prepare sustainability plans post-funding. Support in the form of education, training, and strengthened regulations is crucial to creating an inclusive and sustainable creative economy ecosystem. By overcoming these challenges, crowdfunding has the potential to be an effective tool for promoting innovation and growth in Indonesia’s creative economy sector, while empowering communities to actively contribute to value creation